Rapid degradative effect of microbially synthesized silver nanoparticles on textile dye in presence of sunlight. (April 2018) - Jishma, P.; Narayanan, Rakhie; Snigdha, S.; Thomas, Roshmi; Radhakrishnan, E.K.
Abstract: In the study, the dye collected from industry was identified as methyl violet by LC-MS/MS analysis. The biosynthesized silver nanoparticles (AgNPs) used were characterized by UV–visible spectrophotometry, HR-TEM and FT-IR analysis. Further, the AgNPs were used to evaluate the photocatalytic degradation of methyl violet. The results showed rapid degradation (85.56%) of methyl violet within a period of 20 min in presence of AgNPs and sunlight. The superior photocatalytic activity of AgNPs observed in the study indicates its application for dye degradation. Highlights: Exploration of photocatalytic dye degradation potential of biogenic AgNPs. Eco-friendly nanoparticle synthesis and cost effective degradation. Rapid degradation process under sunlight using AgNPs.